Detecting de novo Hepatic Ketogenesis Using Hyperpolarized [2-13C] Pyruvate - Ragavan, Mukundan; McLeod, Marc A.; Rushin, Anna; Merritt, Matthew E. (Frontiers in Physiology, 2022)
The role of ketones in metabolic health has progressed over the past two decades, moving from what was perceived as a simple byproduct of fatty acid oxidation to a central player in a multiplicity of disease states. Previous work with hyperpolarized (HP) 13C has shown that ketone production can be detected when using precursors that labeled acetyl-CoA at the C1 position, often in tissues that are not normally recognized as ketogenic. Here we assay metabolism of HP [2-13C]pyruvate in the perfused mouse liver, a classic metabolic testbed where nutritional conditions can be precisely controlled. Livers perfused with long-chain fatty acids or the medium chain fatty acid octanoate showed no evidence of ketogenesis in the 13C spectrum. In contrast, addition of dichloroacetate, a potent inhibitor of pyruvate dehydrogenase kinase, resulted in significant production of both acetoacetate and 3-hydroxybutyrate from the pyruvate precursor. This result indicates that ketones are readily produced from carbohydrates, but only in the case where pyruvate dehydrogenase activity is upregulated.